Structural and Biochemical Characterization of Poly-ADP-ribose Polymerase from Trypanosoma brucei - Teemu Haikarainen (Nature Portfolio, 2017)
Abstract Trypanosoma brucei is a unicellular parasite responsible for African trypanosomiasis or sleeping sickness. It contains a single PARP enzyme opposed to many higher eukaryotes, which have numerous PARPs. PARPs are responsible for a post-translational modification, ADP-ribosylation, regulating a multitude of cellular events. T. brucei PARP, like human PARPs-1-3, is activated by DNA binding and it potentially functions in DNA repair processes. Here we characterized activation requirements, structure and subcellular localization of T. brucei PARP. T. brucei PARP was found to be selectively activated by 5′ phosphorylated and 3′ phosphorylated DNA breaks. Importantly, the N-terminal region is responsible for high-affinity DNA-binding and required for DNA-dependent enzymatic activation. This module is also required for nuclear localization of the protein in response to oxidative stress. Solution structures of activating and non-activating PARP-DNA complexes were determined with small-angle X-ray scattering revealing distinct differences in their DNA-binding modes.